Configuration of Ten Light-Harvesting Chlorophyll a/b Complex I Subunits in Chlamydomonas reinhardtii Photosystem I. Issue 2 (20th August 2018) - Ozawa, Shin-Ichiro; Bald, Till; Onishi, Takahito; Xue, Huidan; Matsumura, Takunori; Kubo, Ryota; Takahashi, Hiroko; Hippler, Michael; Takahashi, Yuichiro
Abstract : The stoichiometry and configuration of light-harvesting chlorophyll a/b complex I (LHCI) of Chlamydomonas reinhardtii reveal how 10 LHCI subunits are organized in the PSI supercomplex. Abstract: In plants, the photosystem I (PSI) core complex stably associates with its light-harvesting chlorophyll a / b complex I (LHCI) to form the PSI-LHCI supercomplex. The vascular plant PSI core complex associates with four distinct LHCI subunits, whereas that of the green alga Chlamydomonas reinhardtii binds nine distinct LHCI subunits (LHCA1–LHCA9). The stoichiometry and configuration of these LHCI subunits in the PSI-LHCI supercomplex of C. reinhardtii remain controversial. Here, we determined the stoichiometry of the nine distinct LHCI subunits relative to PSI subunits through uniform labeling of total proteins using 14 C. We separated the nine LHCI polypeptides by three different sodium dodecyl sulfate-polyacrylamide gel electrophoresis systems. Our data revealed that the PSI-LHCI supercomplex contains two LHCA1 proteins and one of each of the other eight LHCI subunits. Subsequently, we identified their cross-linked products by immunodetection and mass spectrometry to determine the configuration of the 10 LHCI subunits within the PSI-LHCI supercomplex. Furthermore, analyses of PSI-LHCI complexes isolated from Ɗ LHCA2 and Ɗ LHCA5 mutants and oligomeric LHCI from a PSI-deficient (Ɗ psaA / B ) mutant provided supporting evidence for the LHCI subunit configuration. In conclusion, eight LHCI subunits bind to the PSI core at the site of PSAF subunit in two layers: LHCA1-LHCA8-LHCA7-LHCA3 from PSAG to PSAK, in the inner layer, and LHCA1-LHCA4-LHCA6-LHCA5 in the outer layer. The other two LHCI subunits, LHCA2 and LHCA9, bind PSAB between PSAG and PSAH, PSAG-LHCA9-LHCA2-PSAH. Our study provides new insights into the LHCI configuration linked to the PSI core.